Analisis Faktor-Faktor Kesulitan Membaca Permulaan Pada Siswa Kelas III C di SDN 193 Pekanbaru - Molinda, Riska; Ain, Siti Quratul (Jayapangus Press, 2025)
This study aims to analyze the factors that contribute to early reading difficulties among third-grade students (Class III C) at SDN 193 Pekanbaru. The research employs a qualitative approach with a case study design. The conceptual framework is based on Jeanne Chall’s theory of early reading development, which views reading ability as the result of interactions between cognitive readiness, literacy environment, and affective support. The research subjects consisted of one homeroom teacher and four students experiencing reading difficulties. Data were collected through observation, interviews, and documentation, and analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that early reading difficulties are influenced by external factors such as limited support from families and inadequate school facilities. This is supported by a student’s statement that they did not have any books at home, which prevented them from practicing reading. Internal factors also play a role, including low reading interest, lack of motivation, underdeveloped social-emotional maturity, and variations in students’ cognitive abilities. These findings are reinforced by the teacher’s observation that students often lose focus while reading and quickly become bored. Efforts made by the teacher include individual guidance, the use of interactive learning strategies, and the provision of positive reinforcement. However, the integration of technology into reading activities remains limited. This highlights the need for greater family involvement and the development of teachers’ capacity to utilize appropriate methods and media to support students’ early reading skills.